Advances in Plant Ethylene Research Proceedings of the 7th International Symposium on the Plant Hormone Ethylene - Ramina, Angelo; Chang, Caren; Giovannoni, Jim.; Klee, Harry; Perata, Pierdomenico; Woltering, Ernst; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2007)
The rapid advances in elucidating the biosynthesis and mode of action of the plant hormone ethylene as well as its involvement in the regulation of the whole plant physiology made imperative the organization of a series of dedicated conferences. This volume contains the main lectures and poster contributions presented at the 7th International Symposium on the Plant Hormone Ethylene held in Pisa in 2006. The book is organized in seven sections dedicated to 1) Ethylene biosynthesis, perception and signal transduction, 2) Interactions between ethylene and other hormones, 3) Role of ethylene in plant growth and differentiation, 4) Fruit development, ripening and quality, 5) Abscission and senescence, 6) Ethylene involvement in biotic and abiotic stresses, and 7) Biotechnology and applied aspects. The most reputed scientists active in the specific topics contributed with original papers and as editors of the related chapters. This book is expected to be of great interest to scientists, researchers, undergraduate and graduate students, interested in the progress made in plant ethylene research and biotechnology.
Ethylene Biosynthesis, Perception And Signal Transduction -- Interactions Between Ethylene And Other Hormones -- Role Of Ethylene In Plant Growth And Differentiation -- Fruit Development, Ripening And Quality -- Abscission And Senescence -- Ethylene Involvement In Biotic And Abiotic Stresses -- Biotechnology And Applied Aspects.
Keywords: Life sciences; Biotechnology; Agriculture; Developmental biology; Plant science; Botany; Plant genetics; Plant physiology; Life Sciences; Plant Sciences; Plant Physiology; Plant Genetics & Genomics; Agriculture; Biotechnology; Developmental Biology; Electronic books